Systematic assessment and management of obesity-related asthma in children: a practical clinical framework - Patri, Jyothi; Chamarthi, Venkata Sushma; Kapoor, Vishali; Gunasekaran, Vignesh (International Journal of Contemporary Pediatrics, 2026)
Childhood obesity significantly worsens asthma risk, symptom burden, and clinical outcomes, yet consistent, practical guidance for managing this common comorbidity is lacking in routine care. This review outlines a clinically actionable framework for assessing and treating obesity‑related asthma in children, emphasizing Body Mass Index percentile classification, age‑appropriate lung function testing, structured asthma control evaluation, and screening for comorbidities such as sleep‑disordered breathing, reflux, metabolic dysfunction, and mental health concerns. Ongoing management should include regular monitoring of respiratory status, weight trajectory, and comorbidity burden. Effective care requires a dual‑target approach that pairs standard asthma pharmacotherapy with comprehensive, family‑centered weight‑management strategies, including nutrition improvement, increased physical activity, behavioral support, and reduced sedentary time, with pharmacologic weight‑management options reserved for select adolescents with severe obesity. Integrating systematic identification, structured follow‑up, and coordinated treatment can meaningfully improve lung function, asthma control, cardiometabolic health, and overall quality of life for affected children.